BRAND LOYALTY MODEL BASED ON BRAND LOVE AND BRAND TRUST - Asiyah, Siti; Irfayanti, Deni (Institut Teknologi dan Bisnis Asia Malang, 2024)
This research aims to examine the relationship between brand love and brand loyalty through brand trust in BHS brand sarongs. The sample in this study was 100 respondents, with a sampling technique using a non-probability sampling technique, with a purposive sampling technique, namely a technique for determining samples with certain considerations. The analysis method used is the SEM method with SmartPLS. The findings of this research are that brand love has a direct effect on brand loyalty and brand trust, while brand trust has no direct effect on brand loyalty. And brand trust is unable to mediate the relationship between brand love and brand loyalty. The conclusion in this research is that brand trust has no effect on brand loyalty, indicating that even though a brand has high trust, if it is not accompanied by the ability to buy, it is impossible to give birth to brand loyalty. The next finding is that high brand love will give birth to brand loyalty to a brand.